Sleep duration is associated with overnight changes in perceived fatigue in elite women soccer players - Barreira, J.; Brito, J.; Costa, J. A.; Figueiredo, P. (Science and Medicine in Football, 2024)
The current study aimed to describe sleep habits and analyze the associations between sleep indices, changes in perceived fatigue (? Fatigue) and external training load measures in women soccer players during a 7-day training camp. Sixteen elite women soccer players (age: 25.4 ± 3.6 years; mean ± SD) from the Portuguese Women`s National Team participated in the study. Sleep indices (sleep duration and efficiency) were measured using a wrist-worn accelerometer. External training loads measures were measured using GPS devices. Players also reported perceived fatigue using a Likert scale (1 - very, very low to 7 - very, very high) before and immediately after sleep. Players` within-subject coefficient of variation for sleep duration was 5.6%, and 4.6% for sleep efficiency. Individually, 8 players (50%) slept less than 7 h per night throughout the training camp, and the same number of athletes had a sleep efficiency lower than 85%. Similar values (p<0.05) were measured for sleep duration and efficiency between training and match days. A moderate negative within-subjects correlation was found between ? Fatigue and sleep duration (adjusted for pre-sleep fatigue) [r = -0.32; 95% Confidence Interval (-0.51 - -0.08); p = 0.04]. These findings reinforce the importance of sleep in the recovery process of elite women soccer players, showing that more sleep may help to attenuate fatigue.